Transition Metal-Catalyzed C-H Functionalization for the Synthesis of Bioactive Heterocycles - Thakur, Rekha (My University, 2025)
In this thesis we have used directing group assisted, transition metal catalyzed C-H activation, enabling the regioselective functionalization of bioactive molecules. This approach allows for the direct functionalization of multiple C-H bonds in a single reaction through C-H bond activation. We were able to achieve dual C-H bond functionalization of naphthalimide and sequential C-H/ N-H alkene annulation of phenanthroimidazoles. The C2-alkenylation of indoles was achieved by cyclic amide of quinazolinone moiety as a directing group. We developed a library of C-H functionalized bioactive compounds and assessed their potential as anticancer agents. These compounds show promising applications in both therapeutics and materials science.
Keywords: C-H bond activation; Directing groups; Naphthalimide; Phenanthroimidazole; Indolylquinazolinone; G-quadruplex